Vascular risk factors and Alzheimer’s disease - O’Brien, John T (BMC Med, 2014)
Vascular factors are now established risk factors for cognitive decline, both for dementia and its two main subtypes: Alzheimer’s disease (AD) and vascular dementia. Their impact likely goes beyond causing an increase in concurrent vascular pathology, since they have been associated with increasing the risk of degenerative Alzheimer (plaque and tangle) pathology, either by increasing its rate of formation or reducing elimination from the brain, or a mixture of the two. A comprehensive series of reviews published in BMC Medicine, investigates the relationship between AD and cardiovascular diseases and risk factors from a clinical, pathological and therapeutic perspective. Whilst links between vascular factors and AD have clearly been demonstrated at both the clinical and pathological level, the nature of the relationship remains to be fully established and there is a lack of high quality treatment studies examining the extent to which vascular risk modification alters AD disease course. Further longitudinal mechanistic and therapeutic studies are required, especially to determine whether treatment of vascular risk can prevent or delay the onset of AD and/or reduce its rate of clinical progression.